Mechanical and Physiological Examination of Barefoot and Shod Conditions in Female Runners - Paulson, S.; Braun, W. A. (International Journal of Sports Medicine, 2014)
Barefoot running and running using minimalist footwear have become increasingly popular in recent years. Footwear choice may affect running mechanics and the metabolic cost of running. To investigate these factors, 8 well-trained, female distance runners (mean age=20.1±1.4 years) were recruited to participate in the study. Following orientation to testing procedures, subjects completed 3 running economy tests on separate days. Treatment order (barefoot, minimalist footwear and running shoe) was counter-balanced. Each testing session consisted of a 5-min warm-up at 2.24 m · s−1, followed by the 7-min RE test at 3.13 m · s−1. Biomechanical data were collected at the 3-min mark for 10 s, and expired gases were collected from minutes 5–7. One-way repeated measures ANOVA revealed a statistically significant difference for running economy (p=0.04), expressed as relative oxygen uptake per km in the barefoot condition (running shoe: 204.51±2.84; minimalist footwear: 198.21±3.04; barefoot: 193.26±3.62 ml · kg−1· km−1) vs. running shoe. The other physiological and biomechanical variables were not statistically significant (p>0.05). However, moderate to large effect sizes suggested there were biomechanical changes that ensured between conditions. It should be further evaluated whether these mechanical adjustments and the running economy trend would translate into improved distance race performance while running barefoot or with minimalist footwear.
Keywords: running economy; minimalist footwear; gait mechanics